Hubungan antara Status Gizi, Aktivitas Fisik, dan Kualitas Tidur dengan Daya Ingat Sesaat pada Anak Usia Sekolah di SD Negeri Semplak 2, Bogor, Jawa Barat: Correlation Between Nutritional Status, Physical Activity, and Sleep Quality with Short-Term Memory in School-Aged Children in SD Negeri Semplak 2, Bogor, West Java - Fahrezi, Handika Firmana Juan; Ekayanti, Ikeu (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Short-term memory in school-aged children can be influenced by several factors, including nutritional status, physical activity levels, and sleep quality. This study aims to analyze the differences and correlations between individual and family characteristics—such as age, allowance, family size, family income, parental education—as well as nutritional status, physical activity, and sleep quality, with short-term memory in school-aged children at SDN Semplak 02. This research used a cross-sectional design with a sample of 40 school-aged children. The sample was selected using a stratified random sampling method. Most subjects had normal nutritional status, engaged in low levels of physical activity, had good sleep quality, and exhibited excellent short-term memory. The results showed significant correlations between individual and family characteristics and short-term memory (p<0.05). There were significant differences in nutritional status, physical activity, and sleep quality based on gender (p<0.05). Significant correlations were found between physical activity and sleep quality with nutritional status (p<0.05). Additionally, there were significant correlations between nutritional status, physical activity, and sleep quality with short-term memory (p<0.05).